"Getting into it": People with intellectual disabilities' experiences and views of Behavioural Activation and Guided Self‐Help for depression. Issue 4 (14th February 2019) - Knight, Roseanna; Jahoda, Andrew; Scott, Katie; Sanger, Kevanne; Knowles, Dawn; Dagnan, Dave; Hastings, Richard P.; Appleton, Kim; Cooper, Sally‐Ann; Melville, Craig; Jones, Rob; Williams, Chris; et al.
Abstract: Background: No studies have explored the acceptability of Behavioural Activation and Guided Self‐Help interventions for depression with people who have intellectual disabilities. Method: Twenty‐five participants were purposively sampled from participants taking part in a trial comparing Behavioural Activation with a Guided Self‐Help intervention. A framework analysis was used to analyse interviews covering participants' expectations and views of therapy. Results: Participants were largely positive about both interventions. However, they identified specific aspects of each intervention which they had found helpful. All participants valued the therapeutic relationship. The participants also had a number of criticisms and suggestions for improving the therapies. A common concern was the time‐limited nature of the interventions and a wish for longer‐term help. Overall, both sets of participants felt the interventions had relevance for their wider lives. Conclusions: The participants reported having positive engagement with the therapies but expressed a wish for longer‐term supportive relationships.